2017
DOI: 10.1002/wcc.481
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐relevant behavioral spillover and the potential contribution of social practice theory

Abstract: Urgent and radical transition to lower-carbon forms of society is imperative to limit current and future climate change impacts. Behavioral spillover theory offers a way to catalyze broad lifestyle change from one behavior to another in ways that generate greater impacts than piecemeal interventions. Despite growing policy and research attention, the evidence for behavioral spillover and the processes driving the phenomenon are unclear. The literature is split between studies that provide evidence for positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(172 citation statements)
references
References 163 publications
(312 reference statements)
6
154
1
1
Order By: Relevance
“…Their analysis found that scientific experts in charge of distributing engagement funding directed 96% of funds to projects deemed primarily reliant on deficit‐based means. This tendency is similarly evident with regards to climate change, in which deficit‐bound communications are by far the dominant means of experts–publics interactions explored within the literature (Editorial, ; Hawkins & Kanngieser, ; Hewitt, Stone, & Tait, ; Kahan & Carpenter, , ; Nash et al, ; van der Linden et al, ; van Renssen, ).…”
Section: Discussion: Relationship Buildingmentioning
confidence: 88%
“…Their analysis found that scientific experts in charge of distributing engagement funding directed 96% of funds to projects deemed primarily reliant on deficit‐based means. This tendency is similarly evident with regards to climate change, in which deficit‐bound communications are by far the dominant means of experts–publics interactions explored within the literature (Editorial, ; Hawkins & Kanngieser, ; Hewitt, Stone, & Tait, ; Kahan & Carpenter, , ; Nash et al, ; van der Linden et al, ; van Renssen, ).…”
Section: Discussion: Relationship Buildingmentioning
confidence: 88%
“…However, positive spillover is also possible, for example, if energy reductions in one area lead a person to look for additional opportunities to conserve, especially when behavior becomes tied to an underlying identity (Gillingham, Kotchen, Raposn, & Wagner, 2013;Nash et al, 2017). While LIMITING CLIMATE CHANGE 6 research is ongoing, no strong evidence currently exists for substantial negative spillover (Maki et al, 2019).…”
Section: The Role Of Individual and Household Behaviormentioning
confidence: 99%
“…The SPT ontology is that the world is populated by social practices and their interconnected elements, while socio-psychology theories are focused on individuals and their behaviours [16]. While we acknowledge this to be true, we do not discount the usefulness of both theories in providing insight into resource consumption patterns and practices of individuals, homes, communities and societies [92]. In fact, researchers are beginning to incorporate these theories into new models.…”
Section: Chalk and Cheese Debatementioning
confidence: 97%